A STUDY OF B.ED. TRAINEES’ ATTITUDES TOWARD THE USE OF DIGITAL DEVICES - Sharma, Pramod Kumar; Kumari, Shakuntala (International Journal of Research -GRANTHAALAYAH, 2024)
The current study analyzed the attitudes of B.Ed. trainees studying in teacher training colleges toward the use of digital devices. The results revealed no significant difference in attitudes between rural and urban students, as digital technology is equally accessible in both areas. However, the attitudes of rural students were more positive than those of female students, likely due to boys’ greater access to technological tools. In contrast, urban female students exhibited a more positive attitude than female students, as they receive ample opportunities to use technological resources alongside their education. The study clearly demonstrates that B.Ed. trainees’ attitudes toward digital devices are more positive. Trainees’ attitudes are influenced by social, geographical, and gender factors.